PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. BPRS BERKAH DANA FADHILILAH AIR TIRIS KAMPAR - mustika, aai (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The Effect of service quality on customer satisfaction at PT. BPRS Berkah Dana Fadhililah Air Tiris Kampar. The purpose of this study was to determine the effect of service quality on customer satisfaction at PT. BPRS Berkah Dana Fadhililah Air Tiris Kampar. The sample in this study were 99 people taken randomly. The survey results in the field obtained the level of customer service quality seen from the five dimensions of assessment (Tangible - Physical appearance, Responsiveness - Speed, Assurance - guarantee, Reliability - Performance, Empathy - care) at PT. BPRS Berkah Dana Fadhililah Air Tiris Kampar, from the results of the analysis of the five dimensions, the Empathy dimension (Service to customers does not distinguish social status) is the most dominant according to the responses of respondents with an average of 4.64. Regression equation obtained by Y = 24.298 + 0.541X, testing the hypothesis with t_count 6.518 (greater than t table ie 1.984) and P-Value <0.05 (0.00 <0.05) then Ho is rejected, while the coefficient of determination is 30.5%, meaning 30.5% satisfaction customers affected by the remaining service quality 69.5% are influenced by other factors.